Serum Level of Transferrin Unique Peptide Is Decreased in Patients With Acute Ischemic Stroke - Hu, Xizheng; Li, Yinghui; Cheng, Peng; Wu, Anhua; Li, Guangyu (Frontiers in Neurology, 2021)
Objectives: Free irons are transported into brain tissues by transferrin and play an important role in neuronal/glial cell damage. Lower serum levels of transferrin have been found in patients with ischemic stroke, compared with healthy subjects. In present study, we investigated whether transferrin unique peptide (TF-UP) could be employed as a serum biomarker for brain tissue damage in acute ischemic stroke. Methods: The venous blood samples of 94 ischemic stroke patients and 35 brain tumor-stroke mimics (BT-SM) patients were collected in the emergency room. Total TF-UP and total albumin unique peptide (Alb-UP) were identified with liquid chromatography/mass spectrometry (LC–MS/MS) and quantified by multiple reaction monitoring (MRM) method using labeled reference peptide (LRP) for further analysis. Results: Median ratio of total TF-UP/LRP was 0.85 (Interquartile range, 0.21) in the brain tumor-stroke mimics (BT-SM) group, and 0.45 (0.14) in the ischemic stroke group; median Alb-UP/LRP ratio was 0.66 (0.16) in the BT-SM group, and 0.55 (0.20) in the ischemic stroke group. The overall trend from low to high levels was statistically significant for TF-UP/LRP (P < 0.0001), but not for Alb-UP/LRP (P = 0.1667). According to the receiver operating characteristic (ROC) curve, the area under the curve (AUC) was 0.9565 and the optimal cutoff value of serum TF-UP was 0.6317, which yielded a sensitivity of 91.49% and a specificity of 88.57%. The odds ratio (95% confidence intervals) of serum TF-UP/LRP was 83.31 (23.43, 296.22, P < 0.0001). Conclusions: Serum TF-UP/LRP level is decreased in patients with acute ischemic stroke in comparison with brain tumor, and it may serve as a serum biomarker for the neuronal/glial cell damage in cerebral infarction.